2015
DOI: 10.1152/ajpcell.00089.2015
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac glycosides induced toxicity in human cells expressing α1-, α2-, or α3-isoforms of Na-K-ATPase

Abstract: Cherniavsky Lev M, Karlish SJ, Garty H. Cardiac glycosides induced toxicity in human cells expressing ␣1-, ␣2-, or ␣3-isoforms of Na-K-ATPase. Am J Physiol Cell Physiol 309: C126 -C135, 2015. First published May 20, 2015 doi:10.1152/ajpcell.00089.2015.-The Na ϩ -K ϩ -ATPase is specifically inhibited by cardiac glycosides, some of which may also function as endogenous mammalian hormones. Previous studies using Xenopus oocytes, yeast cells, or purified isoforms demonstrated that affinities of various cardiac gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 37 publications
(55 reference statements)
2
25
0
Order By: Relevance
“…They demonstrated that apparent affinity of these isoforms for cardiac glycosides differs by less than three-fold, whereas their affinity for marinobufagenin is decreased compared to ouabain by 100–200-fold. More recently, this research team synthesized CTS derivatives whose selectivity for α2- vs. α1-isoform is increased by seven-fold [ 129 , 130 ]. The second hypothesis is consistent with our recent data obtained by isothermal titration microcalorimetry of purified α1β1-isozyme from duck salt glands [ 131 ].…”
Section: Evidence For Na + I K mentioning
confidence: 99%
“…They demonstrated that apparent affinity of these isoforms for cardiac glycosides differs by less than three-fold, whereas their affinity for marinobufagenin is decreased compared to ouabain by 100–200-fold. More recently, this research team synthesized CTS derivatives whose selectivity for α2- vs. α1-isoform is increased by seven-fold [ 129 , 130 ]. The second hypothesis is consistent with our recent data obtained by isothermal titration microcalorimetry of purified α1β1-isozyme from duck salt glands [ 131 ].…”
Section: Evidence For Na + I K mentioning
confidence: 99%
“…Na + /K + -ATPase sub-unit, ATP1A1 is the target of digoxin. 12 Previous study has demonstrated that CGs killed cancer cell through inhibiting ATP1A1. 14 Eskiocak et al have reported that melanomas that expressed higher level of the ATP1A1 were more sensitive to CGs, compared with normal human melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Higher extracellular NaCl concentration was associated with higher expression of ATP1A1 that directly contributed to SCLC's sensitivity towards digoxin ATP1A1 is a subunit of Na + /K + -ATPase. 12 In this study, we further analyzed the expression levels of ATP1A1 among a panel of SCLC cells. Western blotting demonstrated that ATP1A1 was expressed in almost all SCLC cell lines, except for H446 cell line ( Figure 7A).…”
Section: Digoxin Treatment Combined With Nacl Supplement Dramaticallymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting the expression of the alpha1 subunit impaired proliferation and migration in NSCLC cell lines 43 . A recent study has shown that human NSCLC cells overexpressed the alpha1, alpha2, or alpha3 subunits of Na + /K + -ATPase and were induced cell death by cardiac glycosides (i.e., digoxin and ouabain) 44 . In our data, the expression levels of the alpha1 and alpha2 subunits of Na + /K + -ATPase were significantly higher in the hESCs than in the hMSCs or hESC-derived progeny (Figs 1a and 4e).…”
Section: Discussionmentioning
confidence: 99%